The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/1471-3802.12408
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of self‐regulation strategies to improve academic outcomes of students with EBD

Abstract: Self‐regulatory interventions have demonstrated numerous benefits for helping improve the academic performance of students. The purpose of this review was to report on the effectiveness and focus of academic self‐regulation interventions for children and adolescents with emotional and behavioural disorders. Thirty‐six studies published in 35 papers and involving 189 participants met inclusionary criteria. Overall, self‐regulation interventions showed moderate/medium effect size gains [percentage of nonoverlapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 82 publications
1
43
0
Order By: Relevance
“…In the area of math interventions for students with EBD, Popham and colleagues (2018) found moderately positive effects for self-mediated interventions. Positive effects were also reported by Ralston, Benner, Tsai, Riccomini, and Nelson (2014), who also reported that multielement strategy interventions were more effective than single-element counterparts.…”
Section: Improving Outcomes In Ebd Through Self-mediated Mathematic Imentioning
confidence: 98%
See 2 more Smart Citations
“…In the area of math interventions for students with EBD, Popham and colleagues (2018) found moderately positive effects for self-mediated interventions. Positive effects were also reported by Ralston, Benner, Tsai, Riccomini, and Nelson (2014), who also reported that multielement strategy interventions were more effective than single-element counterparts.…”
Section: Improving Outcomes In Ebd Through Self-mediated Mathematic Imentioning
confidence: 98%
“…Common types of self-mediated interventions include goal setting, self-evaluation, self-instruction, self-monitoring, and strategy instruction. Recent systematic reviews of the research literature have identified self-mediated interventions as effective in improving the in-school academic performance of students with EBD (Farley, Torres, Wailehua, & Cook, 2012; Popham, Counts, Ryan, & Katsiyannis, 2018). These interventions were equally effective across elementary, middle, and high school students with EBD.…”
Section: Self-mediated/regulated Interventions To Improve In-school Amentioning
confidence: 99%
See 1 more Smart Citation
“…Authors in this special series have done an exceptional job of connecting it to the practices that they describe. Following are four examples of research summaries that practitioner readers can locate to gain deeper knowledge of the breadth and depth of reading research targeting students with or at risk for EBD: (a) McKenna et al (2017) visually analyze outcomes of single case study reading interventions for students with and at risk for EBD across all grades; (b) Roberts and colleagues (2019) analyze outcomes of reading interventions for students with co-occurring reading and behavioral difficulties; (c) Dunn et al (2017) analyze the quality of peer-mediated interventions for students with EBD; and (d) Popham et al (2018) report on the quality and outcomes of self-regulation interventions for students with EBD. A critical main outcome coming from a review of each of these summary’s findings is that the effects of reading intervention were positive, meaning reading improvement is very much possible for students receiving interventions that are implemented as designed.…”
Section: Glass Half Fullmentioning
confidence: 99%
“…Unfortunately, and providing added rationale for publication of reading-focused intervention articles, observational research continues to suggest that students with EBD fail to receive effective, efficient, and research-based reading instruction (McKenna & Ciullo, 2016). On a positive note, the Burke et al (2015) and Garwood (2018) reviews, along with others (McKenna, Kim, Shin, & Pfannenstiel, 2017;Popham, Counts, Ryan, & Katsiyannis, 2018) suggest that implementation of research-based interventions can have a positive impact on measurable and meaningful outcomes for students with EBD. Reading interventions demonstrating positive reading (and writing) outcomes included direct instruction reading programs and those individually incorporating repeated reading, graphic organizers/cognitive mapping, self-regulation strategies, or listening while previewing.…”
Section: Editorialmentioning
confidence: 99%